Nyai Walida Sebagai Tokoh Pendidikan Nasional - Candra Rizki Dwi Safitri; Budi Haryanto (Journal of Islamic and Muhammadiyah Studies, 2020)
This study aims to determine the historical ways of Nyai Walida's services as a female figure who championed women's equality and early childhood education in the 20th cen- tury through the organization he founded (Aisyiyah) with KH Ahmad Dahlan. This research uses a literature study approach. The data collection technique uses literature study tech- niques which are guided by heuristic understanding. The results of this study aim to provide reinforcement that the existence of Nyai Walida has a strong reason with the pro- posed clause covering independence, integrity, and the sustainability of the ideas of Nyai Walida, which has survived until now. So, Nyai Walida reasoned that she was ordained as a national education figure